The Use of Educational Videos to Improve Student Motivation in the Physical Education Classroom : El uso de videos educativos para la mejora de la motivación del alumnado en el aula de educación física (Papeles, 2023)
Introduction: One of the main problems faced in Physical Education classes is the low motivation of students to perform the exercises indicated by the teacher. The objective of the article is to present the process that was developed and later to present the implementation of a set of educational videos to accompany the Physical Education courses in a public institution located in a municipality in the northeast of Colombia. On the other hand, the implementation of pedagogical methodologies mediated by information and communication technologies has shown positive results to improve student motivation in various areas of knowledge. Methodology: Thus, this work presents the results of an experimental design, where a series of educational videos were used to improve motivation in the Physical Education class. Thirty-one students between the ages of 16 and 18 (M = 16,48, SD = 0.67) participated in the study; 16 students (7 men and 19 women) participated in the control group and 15 students (9 men and 19 women) participated in the experimental group. 6 women). Results and discussion: The results indicate that using the videos significantly improved the motivation of the students with whom they performed the respective exercises. Conclusions: These results are promising and represent an incentive to continue replicating this type of activities that enrich Physical Education classes.
Keywords: Situated learning; physical education; motivation; learning outcomes; relationship; information and communication technologies (ICT)